RESOLUTION OF HOUSING DISPUTES IN THE CIVIL PROCESS - Erdeshova, Zh.I.; Sarsenova, A.B.; Tazhigalieva, M.Zh. (Academic Journal of Physical and Chemical Sciences, 2018)
To date, new norms have been adopted that lay the foundation for the implementation of the new Civil Procedure Code. The aim of the article was to describe the mediation as a legal phenomenon of decisive housing disputes and the identification of its practical procedural resource. Negotiations between the parties while the case was in court proceedings were always conducted, but for obvious reasons they should have been conducted outside the framework of the proceedings. In the process orbit, the result of the negotiation relationship could be manifested - the conclusion of a settlement agreement, subject to approval by the court. Having determined the specifics of a legal phenomenon, its place in a number of other judicial procedures (settlement of the dispute by the court on the merits, conclusion of a settlement agreement, execution of the decision), it is possible to designate a practical framework for the application of mediation rules